2005
DOI: 10.1121/1.2033569
|View full text |Cite
|
Sign up to set email alerts
|

Whistles of small groups of Sotalia fluviatilis during foraging behavior in southeastern Brazil

Abstract: Whistle emissions were recorded from small groups of marine tucuxi dolphins (Sotalia fluviatilis) in two beaches located in an important biological reserve in the Cananéia estuary (25 degrees 03'S, 47 degrees 58'W), southeastern Brazil. A total of 17 h of acoustic data was collected when dolphins were engaged in a specific feeding foraging activity. The amount of 3235 whistles was recorded and 40% (n=1294) were analyzed. Seven acoustic whistle parameters were determined: duration (ms), number of inflection poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Ten acoustic parameters measured from each selected whistle were dictated by its structure: duration (ms), start and end frequency (Hz), minimum and maximum frequency (Hz), frequency range (Hz), frequency at 1/4, 1/2 and 3/4 of duration (Hz), and number of inflection points. An inflection point is a change in the slope of the whistle contour from negative to positive, or vice versa (Pivari and Rosso, 2005). These whistle parameters were chosen both for consistency with previous acoustical studies (for example Erber and Simao, 2004;Bazúa-Durán, 2004;Morisaka et al, 2005;Pivari and Rosso, 2005;Azevedo et al, 2007;Baron et al, 2007), and because they could be easily measured manually from a spectrogram.…”
Section: Quantitative Measurement Of Whistle Acoustic Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten acoustic parameters measured from each selected whistle were dictated by its structure: duration (ms), start and end frequency (Hz), minimum and maximum frequency (Hz), frequency range (Hz), frequency at 1/4, 1/2 and 3/4 of duration (Hz), and number of inflection points. An inflection point is a change in the slope of the whistle contour from negative to positive, or vice versa (Pivari and Rosso, 2005). These whistle parameters were chosen both for consistency with previous acoustical studies (for example Erber and Simao, 2004;Bazúa-Durán, 2004;Morisaka et al, 2005;Pivari and Rosso, 2005;Azevedo et al, 2007;Baron et al, 2007), and because they could be easily measured manually from a spectrogram.…”
Section: Quantitative Measurement Of Whistle Acoustic Featuresmentioning
confidence: 99%
“…Secondly, throughout the entire study period, whistles were never recorded in presence of more than one group of bottlenose dolphins in the area. The inclusive definition of a dolphin focal group, to account for all individuals producing sound, was employed (Wang et al, 1995a(Wang et al, , 1995bErber and Simao, 2004;Bazúa-Durán, 2004;Morisaka et al, 2005;dos Santos et al, 2005;Boisseau, 2005;Pivari and Rosso, 2005;Azevedo et al, 2007;Baron et al, 2007;Quick and Janik, 2008) because during this study was not possible to ascertain which dolphin produced a whistle.…”
Section: Data Collectionmentioning
confidence: 99%
“…The species occurs in bays, estuaries, river mouths, and shallow coastal waters along the western Atlantic Ocean from Southern Brazil to Northern Nicaragua, and possibly Honduras ͑da Silva and Best, 1996;Carr and Bonde, 2000;Edwards and Schnell, 2001;Flores, 2002͒. Despite the relatively broad distribution of the species most of what is known about its acoustic behavior and biology is from populations along the Brazilian coast from which echolocation clicks, pulsed sounds ͑e.g., calls and gargles͒, and whistles have been described ͑e.g., Wiersma, 1982;Terry, 1983;Monteiro-Filho and Monteiro, 2001;Azevedo and Simão, 2002;Erber and Simão, 2004;Azevedo and Van Sluys, 2005;Rossi-Santos and Podos, 2006͒. Whistles are the most studied sound type, and several whistle acoustic variables have been recently described from Brazilian populations ͑Monteiro-Filho and Monteiro, 2001; Azevedo and Simão, 2002;Erber and Simão, 2004;Azevedo and Van Sluys, 2005;Pivari and Rosso, 2005;Rossi-Santos and Podos, 2006͒. Monteiro-Filho and Monteiro ͑2001͒ first described Guyana dolphin whistles as low in frequency ͑up to 6 kHz͒ but a more extensive study revealed a much wider whistle frequency range ͑1.34-23.89 kHz͒ ͑Azevedo and Van Sluys, 2005͒.…”
Section: Introductionmentioning
confidence: 97%
“…The negative correlation between the average number of estuarine dolphins and the pluviometric index may indicate that the sound of rain hitting the water could mask their whistles, making communication between these animals difficult, by comprising a similar sound frequency (GERSTEIN 2002, PIVARI & ROSSO 2005. When this takes place during foraging, estuarine dolphins move to deeper waters, where the sound of rain is not so strong.…”
Section: Revista Brasileira Dementioning
confidence: 99%